Development of a recovery process of thorium and possible separation of rare earths from Korean monazite. Issue 5 (2nd November 2022) - Jeon, Jong Hyuk; Cueva Sola, Ana Belen; Park, Gyu Beom; Lee, Jin-Young; Kim, Hong-in; Jyothi, Rajesh Kumar
ABSTRACT: Systematic studies were carried out to leach out rare earths and recover thorium from Korean monazite. Monazite was processed with acid baking process (sulfation) where rare earth elements (REEs) and thorium phosphates were transformed to water-soluble sulfates. Various experimental factors such as temperature, H2 SO4 /monazite concentrate ratio and time were studied to get optimized sulfation system. Near to 88% of leaching of REEs and Th was performed after sulfation followed by water leaching. Moreover, by using 0.1 mol/L of primary amine Primene JM-T (tri-alkyl-methylamine), thorium was separated (more than 95%) from the light rare earth elements present in the leach liquor. Subsequently, rare earth elements were separated by solvent extraction technique using Cyanex 572 as an extractant at different pH conditions. High separation coefficients for different rare earths were obtained with Cyanex 572, while Primene JM-T resulted in the complete separation of the thorium from the leach liquor.